2009
DOI: 10.3855/jidc.334
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori DNA in gallbladder tissue of patients with cholelithiasis and cholecystitis

Abstract: Background: Earlier reports on the detection of H. pylori DNA in gallbladder tissue of patients with cholelithiasis and cholecystitis gave discordant results. Our aim was to detect the presence of H. pylori DNA and to determine whether a correlation can be established with the biliary diseases. Methodology: The study included a total of 68 patients 20 to 79 years of age. Fifty-three of the participants were females, of whom 33 had cholelithiasis and 20 did not. Out of the 15 male patients, 8 were had cholelith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…With heterogeneity ( I 2  = 69.5%, P<0.0001), the cumulative odds ratio for the sample was 2.59 (95% CI 1.21–5.55) and favored the role of H. Pylori in lithiasis cases (Figure 1). A sensitivity analysis omitting 1 study at a time and calculating the pooled ORs for the remainder of the studies showed that the two study by Yucebilgili [34] and Figura [22] might substantially influence the pooled OR. After excluding these two studies, there was no heterogeneity detected.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…With heterogeneity ( I 2  = 69.5%, P<0.0001), the cumulative odds ratio for the sample was 2.59 (95% CI 1.21–5.55) and favored the role of H. Pylori in lithiasis cases (Figure 1). A sensitivity analysis omitting 1 study at a time and calculating the pooled ORs for the remainder of the studies showed that the two study by Yucebilgili [34] and Figura [22] might substantially influence the pooled OR. After excluding these two studies, there was no heterogeneity detected.…”
Section: Resultsmentioning
confidence: 99%
“…Four techniques including ELISA [8], [22], [28], PCR [8], [24], [25], [27][31], [33]–[35], [37], immunohistochemistry staining (IHC) [30], [37] and culture [27], [30], [31], [34] were utilized for identifying the presence of H. Pylori (Table 3). ELISA was performed in three studies in order to detect the H. Pylori -specific IgG in serum samples.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This figure agrees with 2 other studies identifying DNA of Helicobacter spp. in 22%-27.7% of gallbladder samples [15,16]. While Silva et al detected Helicobacter DNA in gallbladder tissue in 31.3% of their cases, they pointed out the possibility that H. pylori had Table 1 colonized a previously damaged epithelium [13].…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, the result of two different studies in Korea and Hong Kong did not find any role for Helicobacter species in the pathogenesis of biliary disease [20,21], concluding that Helicobacter infection may not play a significant role in the formation of gallstones. In addition, Neri et al [22] and Yucebilgili et al [23] found that, although H. pylori DNA was detected by PCR in gallbladder tissue of patients with cholecystitis, a clinical correlation with biliary disease could not be established.…”
Section: Discussionmentioning
confidence: 97%